Round Trip Time Evaluation Of Padangbai - Nusa Penida Crossing Vessels To Improve Performance At Roro Ferry In Bali Province - Nurochman, Khafid; Khairani, Muhammad; Djulfi, Isman; Taufiqurrahman, Muhammad; Syahputra Ambarita, Jogi Ogun (IWJ : Inland Waterways Journal, 2023)
Padangbai Harbor is a port located in a village in Manggis District, Karangasem Regency, on the east side of Bali Island, Indonesia. Padangbai Port is a port that serves ship crossings from Bali to Lombok and Nusa Penida and vice versa serves ships heading to Bali. The Padangbai ferry port is a very busy ferry port because it has 2 routes, namely the Padangbai-Sheet route and the Padangbai-Nusa Penida route. There are 25 ships operating on the Padangbai - Selamat route, of which 2 ships belong to ASDP and 23 privately owned ships and 1 ship on the Padangbai - Nusa Penida route belongs to the Klungkung Regency Government. The Padangbai Ferry Port also has a schedule made by the Bali Class II Transportation Management Agency. However, there is a mismatch between the ship's arrival and departure times and the schedule that has been made. This research is research using qualitative methods. Based on the results of the analysis of problems in scheduling departures and arrivals at the Padangbai Ferry Port, delays of 20 minutes were still found which caused delays in the ship's onward performance. Therefore, it is very necessary to evaluate the ship's round trip time to improve performance at the Padangbai Ferry Port.